Effect of freshwater on plant species diversity and interspecific associations in coastal wetlands invaded by Spartina alterniflora - Dou, Zhiguo; Cui, Lijuan; Li, Wei; Lei, Yinru; Zuo, Xueyan; Cai, Yang; Yan, Rui (Frontiers in Plant Science, 2022)
Plant invasions can lead to the degradation of coastal wetland vegetation. Freshwater can facilitate the restoration of coastal wetland vegetation by restricting the spread of invasive plants. The present study was to evaluate the effects of freshwater on the characteristics of vegetation communities in coastal wetlands invaded by Spartina alterniflora. Two field investigations was conducted in 2008 and 2018, before and after the introduction of the freshwater. The characteristics of the vegetation communities were analyzed by hierarchical cluster analysis and compared by using several diversity indices. In addition, the differences in habitat community composition and interspecific relationships of dominant species were analyzed. The results showed that the overall plant species diversity of coastal wetlands invaded by S. alterniflora was low. The plant species diversity was increased after freshwater been introduced in the study site. However, the results were reversed in the area without freshwater introduction. Freshwater introduction often changes the interspecific relationships between Suaeda salsa and the other species. The intensified invasion of S. alterniflora changed the interspecific relationship of native halophytes from negatively related to positively related. Although freshwater effectively inhibited the further invasion of S. alterniflora, it also brought the risk of the expansion of the glycophyte vegetation community. The outcomes of this study highlight the necessity of early intervention for restoration measures, which can adopted to coastal wetland restoration, the preservation of biodiversity, and the management of plant resources.